Evaluating Geomorphic Features as Surrogates for Benthic Biodiversity on Australia's Western Continental Margin - Althaus, F.; Williams, A.; Kloser, Rudy; Seiler, J.; Bax, N. (2012)
Australia's western continental margin extends over~2,000 km, from subtropical to temperate latitudes (~18-35. oS). The regional oceanography overlying the deep continental shelf and slope area (~100-1,000 m depths) is profoundly influenced by the southward-flowing Leeuwin current (LC) to depths of ~300 m, and by a northward-flowing counter-current, the Leeuwin Undercurrent (LUC) below those depths. The LC is characterized by warm, low-salinity, low-productivity waters, whereas the LUC is characterized by colder more oxygenated waters. The role of these features as ecological habitats and their potential as surrogates for biodiversity were examined in the context of a hierarchical habitat classification scheme used by Last et al. to define bioregions for marine management planning in Australian waters. Associations of epibenthic megafauna with habitats along Australia's western margin were evaluated quantitatively summarizing the presence/absence scores of 11 fauna types in the video frames into percentage occurrences of dominant fauna for each sample. The scored fauna types were: sessile fauna absent, bioturbators, anemones, seapen, stalked sponge, ascidians, bryozoa, crinoids, sponges, coral, and coral (reef); all scored at low or high abundance. It is necessary to have information at coarser scales to provide ecologically meaningful context, while information at finer scales provides ecologically meaningful detail. © 2012 Elsevier Inc. All rights reserved.